Harmonic Text-Painting in Franz Liszt’s Lieder - Richard Bass; Heather de Savage; Patricia Grimm (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
Despite their effectiveness and general appeal, Liszt’s Lieder have not attracted the same level of interest among scholars and analysts as those of other first-rank composers of the nineteenth century. Liszt’s innovative approach to harmony, which includes a high degree of chromaticism and enharmonic shifts, along with frequent changes of tonal focus and tonal ambiguity, often frustrates efforts at analysis that attempt to reveal unified tonal structures. These factors have encouraged a view of this repertoire as uneven or inconsistent. In this study we explain Liszt’s distinctive approach to text setting as a dichotomy between traditional and progressive tonal-harmonic practices that parallels the contrasts between Classical and Romantic aesthetics and related ideas and images that operate within the poetry. We demonstrate, through the examination of surface-level harmonic progressions as well as large-scale tonal relationships, how Liszt’s Lieder reflect the conflicts and contradictions between these two sets of ideas, and the search for understanding or resolution. Analyses of individual songs illustrate both the richness and the consistency of Liszt’s harmonic style, in conveying and interpreting the meaning of texts dealing with common Romantic subjects.